Emotions in History - Lost and Found - Ute Frevert (Central European University Press, 2011)
Coming to terms with emotions and how they influence human behaviour, seems to be of the utmost importance to societies that are obsessed with everything "neuro." On the other hand, emotions have become an object of constant individual and social manipulation since "emotional intelligence" emerged as a buzzword of our times. Reflecting on this burgeoning interest in human emotions makes one think of how this interest developed and what fuelled it. From a historian's point of view, it can be t...